2017
DOI: 10.1007/s11356-017-9279-8
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis

Abstract: Acute upper and lower respiratory infections are main causes of mortality and morbidity in children. Air pollution has been recognized as an important contributor to development and exacerbation of respiratory infections. However, few studies are available in China. In this study, we investigated the short-term effect of air pollution on hospital visits for acute upper and lower respiratory infections among children under 15 years in Ningbo, China. Poisson generalized models were used to estimate the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 31 publications
4
26
0
2
Order By: Relevance
“…This may be mainly because of two reasons: first, children's low immune function makes them more susceptible to respiratory infections, and second, previous studies have shown that air pollution may lead to increased respiratory diseases in children. [8][9][10] The Global Burden of Disease 2013 study found that lower respiratory tract infections were the leading cause of hospitalization for children aged 0-19 years in most developing countries, and particularly among children younger than 5 years. 11 Many of the risk factors for respiratory diseases, such as household air pollution and low immunity, are avoidable through proper prevention and management.…”
Section: Discussionmentioning
confidence: 99%
“…This may be mainly because of two reasons: first, children's low immune function makes them more susceptible to respiratory infections, and second, previous studies have shown that air pollution may lead to increased respiratory diseases in children. [8][9][10] The Global Burden of Disease 2013 study found that lower respiratory tract infections were the leading cause of hospitalization for children aged 0-19 years in most developing countries, and particularly among children younger than 5 years. 11 Many of the risk factors for respiratory diseases, such as household air pollution and low immunity, are avoidable through proper prevention and management.…”
Section: Discussionmentioning
confidence: 99%
“…This seasonal discrepancy may be explained by a higher level of air pollutants in cold period as Table 1 shows. Furthermore, residents may reduce time to go outdoors due to high temperature and frequent rain during warm seasons [ 17 ] thus the chance of exposure to ambient air pollution is relatively lower as compared with cold seasons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, contrary to the study by Nhung, stronger associations were observed among older children [ 17 ]. Another study from China also found stronger associations in older children [ 18 ]. Despite mounting literature suggesting that air pollution may be associated with respiratory disease in children, information regarding the association remains limited.…”
Section: Introductionmentioning
confidence: 99%